Proteomics of bronchoalveolar lavage fluid reveals a lung oxidative stress response in murine herpesvirus-68 infection - Bortz, Eric; Wu, Ting-Ting; Patel, Parthive H.; Whitelegge, Julian P.; Sun, Ren (Viruses, 2018)
Murine herpesvirus-68 (MHV-68) productively infects mouse lungs, exhibiting a complex pathology characteristic of both acute viral infections and chronic respiratory diseases. We sought to discover proteins differentially expressed in bronchoalveolar lavage (BAL) from mice infected with MHV-68. Mice were infected intranasally with MHV-68. After nine days, as the lytic phase of infection resolved, differential BAL proteins were identified by two-dimensional (2D) electrophoresis and mass spectrometry. Of 23 unique proteins, acute phase proteins, vitamin A transport, and oxidative stress response factors Pdx6 and EC-SOD (Sod3) were enriched. Correspondingly, iNOS2 was induced in lung tissue by seven days post-infection. Oxidative stress was partly a direct result of MHV-68 infection, as reactive oxygen species (ROS) were induced in cultured murine NIH3T3 fibroblasts and human lung A549 cells infected with MHV-68. Finally, mice infected with a recombinant MHV-68 co-expressing inflammatory cytokine murine interleukin 6 (IL6) showed exacerbated oxidative stress and soluble type I collagen characteristic of tissue recovery. Thus, oxidative stress appears to be a salient feature of MHV-68 pathogenesis, in part caused by lytic replication of the virus and IL6. Proteins and small molecules in lung oxidative stress networks therefore may provide new therapeutic targets to ameliorate respiratory virus infections.
Gesehen am 30.03.2020